The historical influence of nursing organisations on the development of the nursing profession in South Africa - J.M. Esterhuizen; G.H. van Rensburg (Elsevier, 2021)
Guided by critical realism philosophical principles, this historical inquiry describes the factors that influenced the professional nature of South African nursing organisations. It further describes the professional, educational and political functions of nursing organisations over the past century (1914-2014) and illustrates how these organisations influenced the professional development of nursing in South Africa. Data rich primary and secondary literature sources were analysed, and the findings were recorded in narrative form. The researchers concluded that over time, a social class system, religion, political ideology and economic needs reshaped South Africa's nursing organisations and consequently the profession. Determined to create the female professional image, status and educational exclusivity, the nurse leaders of the 20th century opted to establish the first South African professional nursing association. The result was a recognised, respected and trained nursing corps. By the end of the 20th century, however, South African nurse leaders accepted that nurses needed their socio-economic welfare to be prioritised; and a professional organisation with a trade unionist stance was established. The result was a trained, politicised nursing corps struggling to find its collective professional voice. Socio-economic and political status became more important than professional development and the professional image. It is recommended that nurses use their political voices to collectively communicate South African nursing's philosophical principles and values to members of the profession and the society at large. South African nurses should develop a position paper that clarifies the extent to which party-political interests will be allowed to impact decisions about nursing matters.